The Influence of Metabolic Syndrome Risk Factors on Carotid Intima Media Thickness in Children. (January 2021) - Downing, Robert; Michael, Timothy; Place, Rebecca; Hoffman, Eric; Visich, Paul
Pediatric obesity is a major health concern today, which pre-disposes individuals to metabolic syndrome (MS), and the risk of premature cardiovascular disease (CVD). Use of carotid intima media thickness (CIMT) is recognized as non-invasive way to assess vascular health. The objective of this study was to determine which MBS risk factors has an influence on increasing one's risk of an increased CIMT in children. In southern Maine 189 children (age: 10.52 ± .52 years) had their MBS risk factors and CIMT assessed. Based on CIMT, children were divided into quartiles and compared to MBS risk factors. Children in the highest quartile for CIMT had the highest waist circumference ( P  < .05) compared to all other groups, using a one-way analysis of variance. No other MBS risk factors had an influence on CIMT. It appears early identification of children with an elevated WC may be beneficial in identifying children at risk of premature CVD.